'I don't belong anywhere' György Ligeti at 100 - Marx, Wolfgang 1967- (Brepols, 2022)
2023 marks the centenary of Ligeti?s birth, an appropriate moment to take stock of the relevance this composer has in the contemporary world, to assess where he "belongs" today and how our views of his uvre and our understanding of his position in musical and cultural history have evolved. What do Ligeti and his music have to say to us in our post-postmodernist age? Why do his works still fascinate us so much? 0This book offers new readings of core compositions such as "Aventures", "Lontano", "Le Grand Macabre", the "Hölderlin Fantasies" and "Galamb borong". It also reassesses the context and reception of Ligeti?s works, including the influence of Romanian music (not least in his childhood), musical life in Hungary between 1945 and 1956, the ways in which his thinking was influenced by his experience of different soundscapes, yet also the surprisingly widespread use of his music in film and TV (beyond the usual suspect). Finally it presents new sources discovered or made available only recently: letters exchanged between Ligeti and Aliute Mecys in 1972, the correspondence between the composer and his publisher Schott, and an extended BBC interview from 1997.
Keywords: Ligeti, György -- 1923-2006; Festschrift